2019
DOI: 10.1097/mph.0000000000001158
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Therapy in a Patient With Down Syndrome and Refractory Acute Myeloid Leukemia

Abstract: Acute myeloid leukemia (AML) associated with Down syndrome (DS-AML) is a unique entity of AML with superior treatment response and overall survival compared with children with non-DS-AML. Despite good outcomes in DS-AML, those who relapse or have refractory disease have poor survival. Successful treatment of these patients is challenged by increased incidence of treatment-related toxicities often encountered with high-dose chemotherapy. Here we report the experience of epigenetic modifying agents (decitabine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…To date, only single case reports describing treatment with demethylating agents or histone deacetylase inhibitors have been published in patients with DS and refractory or relapsed AML. [ 38 , 39 ]…”
Section: Discussionmentioning
confidence: 99%
“…To date, only single case reports describing treatment with demethylating agents or histone deacetylase inhibitors have been published in patients with DS and refractory or relapsed AML. [ 38 , 39 ]…”
Section: Discussionmentioning
confidence: 99%
“…The first step is a genome-wide hypomethylation directly related to the additional copy of chromosome 21. The second step, detected in TL-DS cells which presented GATA1 mutation, consists in aberrant hypermethylation that affects genes responsible for hematological development and regulation of cell processes such as growth, proliferation, cell cycle regulation and death [23,93,94] (Fig. 10).…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Whole‐exome sequencing revealed that 46% and 33% of ML‐DS blasts contain mutations in cohesin complex genes and epigenetic regulators, respectively . Although these findings suggest potential benefit of epigenetic targeted therapies, the use of demethylating agents or histone deacetylase inhibitors in children with DS has only been reported in anecdotal cases to date and has not been evaluated systematically in clinical trials. As a result, an efficacious or even agreed‐upon standard of care for the treatment of children with relapsed ML‐DS is lacking.…”
Section: Aml In Dsmentioning
confidence: 99%